Students’ Attitudes Towards a Career in the Hospitality Industry - Implications for Cooperation between the Hospitality Sector and Educational Institutions - Bednarska, Marlena (Studia Oeconomica Posnaniensia, 2014)
The hospitality industry is a highly labour-intensive sector that relies on the abilities and intentions of employees to identify and satisfy customers’ needs. Increasing competition within the sector, combined with the significance of the customer-employee interaction in the provision of services, has resulted in the need to intensify efforts to attract and retain qualified and motivated personnel. If companies wish to gain a competitive advantage through recruiting the best available human capital, they should create an image of being an excellent place to work in the minds of potential staff. The objective of this paper is to examine the perceived prospects for career development in the hospitality industry by potential employees, which will help put forward recommendations to the HORECA sector with respect to cooperation with educational institutions. The research was conducted on a group of 335 students enrolled in tourism studies in Poznan. It revealed that students with working experience in the lodging industry perceive a hospitality-related career as more attractive than do those without such experience, are more willing to apply for a job in accommodation establishments, and rate financial and non-financial working conditions in the sector more favourably. This should encourage establishments of the HORECA sector to become involved in cooperative education partnerships.